Case Report: Personalized, functional drug sensitivity-guided chemotherapy achieves long-term disease-free survival in canine pulmonary adenocarcinoma - Yeon, Kyu-Duk; Bae, Kieun; Choi, Jin-Young; Yoon, Kyong-Ah; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2026)
IntroductionCanine pulmonary adenocarcinoma (PAC) is a relatively uncommon primary lung tumor in dogs, with prognosis influenced by clinical stage, histological grade, and surgical margins. Despite surgical resection being the treatment of choice, long-term outcomes remain highly variable, and the benefit of conventional empirically chosen adjuvant chemotherapy remains limited, especially in high-risk cases.MethodsA 10-year-old spayed female Maltese dog presented with a solitary pulmonary mass was diagnosed with moderately differentiated PAC after complete (R0) resection via right middle lung lobectomy. Given the tumor’s histological grade and suspected nodal involvement, ex vivo functional drug sensitivity testing using patient-derived tumor cells and three-dimensional organoid culture was performed to guide personalized chemotherapeutic selection.ResultsDoxorubicin and toceranib exhibited the highest cytotoxicity and were sequentially administered as adjuvant therapy. The patient tolerated the treatment well without notable adverse effects, and serial thoracic imaging over 548 days revealed no evidence of recurrence or metastasis.ConclusionThis case highlights the clinical utility of integrating functional drug sensitivity testing and organoid validation into personalized chemotherapy decision-making for canine PAC, demonstrating prolonged disease-free survival exceeding 500 days in a patient with intermediate-grade histology and suspected nodal involvement.